2017
DOI: 10.1002/slct.201701695
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mesoporous Biomass Carbon Derived from Corn Stalks and Formation Mechanism

Abstract: Different formational process could lead to diverse morphologies and properties. Therefore, the study on formation mechanism was very important to figure out the influence of formational process. The corn stalk core (CSC), as a kind of renewable biological resource, could be used as raw materials to prepare activated carbon materials (ACs) via carbonizing and activating. The transformational mechanisms on the every step and the variation of various components in the CSC were studied, which was supposed the fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Vast pore structures could be obtained by removing the templates from the final products. Moreover, some of these BET surface area and pore volume values were higher than those of some reported biomass derived mesoporous carbons such as corn stalks derived mesoporous carbon with a 737 m 2 /g surface area (Yu et al 2017) produced via pyrolysis and activation. β-Cyclodextrin-derived mesoporous carbons with the highest BET surface area and pore volume of 860 and 0.46 cm 3 /g, respectively (Xin et al 2017) and hydroxymethyl furfural derived mesoporous carbon with a specific surface area of 451 m 2 /g and pore volume of 0.36 cm 3 /g (Wang et al 2016) from hydrothermal method have been reported.…”
Section: Characterizationmentioning
confidence: 69%
“…Vast pore structures could be obtained by removing the templates from the final products. Moreover, some of these BET surface area and pore volume values were higher than those of some reported biomass derived mesoporous carbons such as corn stalks derived mesoporous carbon with a 737 m 2 /g surface area (Yu et al 2017) produced via pyrolysis and activation. β-Cyclodextrin-derived mesoporous carbons with the highest BET surface area and pore volume of 860 and 0.46 cm 3 /g, respectively (Xin et al 2017) and hydroxymethyl furfural derived mesoporous carbon with a specific surface area of 451 m 2 /g and pore volume of 0.36 cm 3 /g (Wang et al 2016) from hydrothermal method have been reported.…”
Section: Characterizationmentioning
confidence: 69%
“…Some representative cases are summarized in Table . Utilizing corn, corn byproducts, and corn industrial products to produce nanostructured carbonaceous materials as anodes has been proposed as well. ,, Some representative cases are summarized in Table . In this section, two representative cases are reviewed in detail.…”
Section: Corn-mediated Carbonaceous Materials As Anodes In Lithium-io...mentioning
confidence: 99%